Kegiatan Marketing Public Relations Terhadap Proses Pengambilan Keputusan Pembelian Apartemen Pada Generasi Milenial - Gunawan Wiradharma; Khaerul Anam; Karina Pramita Ningrum (LUGAS Jurnal Komunikasi, 2020)
The construction and sale of apartments in big cities have increased, leading to competition between companies that sell or lease apartment units. Marketing public relations activities are important in encouraging consumers to attract prospective customers' interest in the decision-making process. The purpose of this research is how the influence of marketing public relations activities on the decision-making process of buying apartments in the millennial generation in an apartment in Depok City in October 2019. This research's indicators are publications, media identity, events, news, speeches, participation in social activities, and sponsorship. The purchase decision-making process indicators are the introduction of needs, information seeking, alternative evaluations, purchasing decisions, and post-purchase behavior. This research method is a quantitative and explanatory survey of tenants/buyers of the period in October 2019. This study concludes that marketing public relations activities positively influence the purchase decision-making process to buy Apartment X units in millennials.